The Effect of Education Expenditure, Health Expenditure, Islamic Bank Financing, And Economic Growth on The Human Development Index in Indonesia - Zakaria, Muhammad Rizki; Rahmawati, Farida; Sulaiman, Nor Fatimah Che (Journal Governance Society, 2025)
The purpose of this research is to analyze the effect of education expenditure, health expenditure, Islamic bank financing, and economic growth on the HDI of Indonesian provinces during the period 2013–2023. Using a quantitative approach, the study employs panel data regression on secondary data from 33 provinces obtained from BPS, OJK, and the Ministry of Finance. The most appropriate estimation model is selected through the Chow and Hausman tests, which both support the use of a fixed effect model, followed by multicollinearity and heteroscedasticity diagnostics to ensure model validity. The results show that education expenditure, health expenditure, Islamic bank financing, and economic growth each have a positive and statistically significant impact on HDI, while jointly explaining approximately 85% of its variation across provinces. These findings suggest that increased education and health budgets effectively enhance human capital through longer schooling, better health outcomes, and higher life expectancy, whereas expanded Islamic bank financing and robust economic growth raise adjusted per capita expenditure and overall welfare. The study concludes that optimizing human development in Indonesia requires a coherent policy mix that strengthens pro-poor and pro-human capital public expenditure, deepens Islamic financial inclusion, and sustains inclusive economic growth, particularly in lagging regions, in order to narrow HDI disparities and support long-term sustainable development.